Emigración reciente de latinoamericanos a España: trayectorias laborales y movilidad ocupacional - Anguiano-Téllez, María Eugenia (Papeles de Población, 2021)
This article analyzes the factors associated with the human capital and the social capital that favor or limit the incorporation of immigrants into the Spanish labor market, exploring the demographic characteristics, family networks and labor trajectories of three Latin American immigrant groups live in Spain: Ecuadorians, Peruvians and Dominicans. The variation in the antiquity of these three flows of immigrants, as well as their demographic profiles and the extension of their familiar networks in Spain have influenced in their enter and mobility in the Spanish labor market. The essay is based on information gathered in a survey conducted by the Instituto Universitario de Estudios sobre Migraciones, Pontificia Universidad de Comillas, Madrid, in 1998. The sample using quotas considered the concentration patterns of immigrants in Spain.